Teaching in a globally-connected world : preparing learners for the future - Sparapani, Ervin F. (Hamilton Books, An imprint of Rowman and Littlefield, 2016)
This book examines the current social, political, economic, and religious climate of the world, makes projections for the future, and then makes suggestions for what the contributors believe educators need to think about in order to adequately prepare young people to successfully navigate that future.